2010
DOI: 10.1111/j.1742-4658.2010.07911.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NADPH oxidase 2 substantially restores glucose‐induced dysfunction of pancreatic NIT‐1 cells

Abstract: Defects in insulin secretion by pancreatic cells and/or decreased sensitivity of target tissues to insulin action are the key features of type 2 diabetes. It has been shown that excessive generation of reactive oxygen species (ROS) is linked to glucose‐induced β‐cell dysfunction. However, cellular mechanisms involved in ROS generation in β‐cells and the link between ROS and glucose‐induced β‐cell dysfunction are poorly understood. Here, we demonstrate a key role of NADPH oxidase 2 (NOX2)‐derived ROS in the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…In pancreatic β-cells, chronic high glucose concentrations are associated with reduced insulin expression, elevated cell stress and apoptosis via oxidative damage delivered from NOX2 activation [67]. However, metabolic overload in vivo is not necessarily associated with NOX2-derived oxidative stress and decreased function of pancreatic β-cells since it was demonstrated that pancreatic islets isolated from rats fed a high-fat diet for 13 weeks had increased pancreatic islet functionality, associated with high levels of glucose metabolism and GSIS, but also low levels of NOX2 expression and ROS production [68].…”
Section: The Role Of Nox In Pancreatic Islet Dysfunction and Possiblementioning
confidence: 99%
“…In pancreatic β-cells, chronic high glucose concentrations are associated with reduced insulin expression, elevated cell stress and apoptosis via oxidative damage delivered from NOX2 activation [67]. However, metabolic overload in vivo is not necessarily associated with NOX2-derived oxidative stress and decreased function of pancreatic β-cells since it was demonstrated that pancreatic islets isolated from rats fed a high-fat diet for 13 weeks had increased pancreatic islet functionality, associated with high levels of glucose metabolism and GSIS, but also low levels of NOX2 expression and ROS production [68].…”
Section: The Role Of Nox In Pancreatic Islet Dysfunction and Possiblementioning
confidence: 99%
“…Islets isolated from Wistar rats fed a high-fat diet for 13 weeks resulted in increased pancreatic islet functionality, associated with high levels of glucose metabolism and GSIS but also low levels of NOX2 expression and ROS production (Valle et al 2011). On the other hand, when Sprague Dawley rats (which are prone to develop insulin resistance and obesity (Reaven & Reaven 1981)) were submitted to a high-fat diet for a longer period (24 weeks), diabetes ensued that was associated with increased islet ROS and reduced insulin expression (Yuan et al 2010). Moreover, human islets isolated from type 2 diabetic patients demonstrated increased mRNA levels of the p22 subunit of NAD(P)H oxidase (Marchetti et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…NOX2, and of other NOX isoforms (NOX1 and NOX4) has been reported in rat pancreatic islets (Oliveira et al, 2003;Uchizono et al, 2006). In β-cells NOX2 appeared to be involved in oxidative stress induced by high chronic glucose levels in glucotoxicity (Yuan et al, 2010). Interestingly, although NOX2 deficiency protected against streptozotocin-induced β-cell destruction (Xiang et al, 2010), the suppression of its activity also impaired the mechanisms of glucose-stimulated insulin secretion (GSIS) in rodent islets (Imoto et al, 2008;Morgan et al, 2009).…”
mentioning
confidence: 95%